mRNA localization and the cytoskeleton. - de Heredia, M.L.; Jansen, R.P. (Current Opinion in Cell Biology, 2004)
mRNA localization is a widespread post-transcriptional mechanism for targeting protein synthesis to specific cellular sites. It is involved in the generation of cell polarity, asymmetric segregation of cell fate determinants and germ cell specification. Actin and microtubule filaments have key functions during RNA localization, especially during transport of mRNAs and anchoring at target sites. Recent advances in understanding the role of motors and filament systems have mainly resulted from the contribution of live imaging of mRNA movement and from the purification of putative localization ribonucleoproteins. There have also been new findings on the role of centrosomes in RNA localization.